2021
DOI: 10.1111/1759-7714.13841
|View full text |Cite
|
Sign up to set email alerts
|

Subsegmental resection preserves regional pulmonary function: A focus on thoracoscopy

Abstract: Background The aim of this study was to evaluate regional postoperative preserved pulmonary function (PPPF) and three‐dimensional (3D) volumetric changes according to the number of resected subsegments and investigate the factors that most affected pre‐/post PPPF. Methods Patients who underwent thoracoscopic lobectomy (n = 73), and segmentectomy (n = 87) were eligible for inclusion in the study. They were classified according to the number of resected subsegments which ranged from 1 to 10. The percentage of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, due to the limited sample size, they did not compare pulmonary function changes after different segmentectomies with the corresponding lobectomies. Kuroda et al detected significant differences in FEV1 preservation after VATS left upper lobe resections between 4 and 5-7 resected subsegments, and between 5-7 and 10 resected subsegments (29). But their study did not embark on resections of other lobes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, due to the limited sample size, they did not compare pulmonary function changes after different segmentectomies with the corresponding lobectomies. Kuroda et al detected significant differences in FEV1 preservation after VATS left upper lobe resections between 4 and 5-7 resected subsegments, and between 5-7 and 10 resected subsegments (29). But their study did not embark on resections of other lobes.…”
Section: Discussionmentioning
confidence: 93%
“…Only a limited number of retrospective small-sample studies have compared functional changes after lobectomy and segmentectomy in the VATS setting (24)(25)(26)(27)(28)(29)(30), among which few explored pulmonary function changes after different segmentectomies (25,29). Tane et al noticed that FEV1 could be better preserved after single segmentectomy than after combined segmentectomy (25).…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing popularity of low-dose spiral computed tomography (CT) screening, the incidence of early clinical T stage lung malignancy has been increasing ( 2 ). As the number of patients with small ground glass nodule increases, more thoracic surgeons have accepted segmental or subsegmental resection and selective lymph node dissection as optimized treatment modalities ( 3 , 4 ). However, there are still some patients with early clinical stage occur lymph node metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, among 26 tumors treated by RFA in this study, lobectomy or segmentectomy were required to treat 21 nodules if surgery was performed. It has been reported that VC and FEV 1.0 decrease 7.1%–19.2% and 8.7%–21.0% after lobectomy and 4.1%–15.0% and 6.2%–18.4% after segmentectomy, 32 , 33 , 34 , 35 respectively. Moreover, bilateral metastasectomy was reported to impair pulmonary function than unilateral surgery.…”
Section: Discussionmentioning
confidence: 99%